Proanthocyanidins with a low degree of polymerization are good inhibitors of digestive enzymes because of their ability to form specific interactions: a hypothesis - Vázquez-Flores, Alma A. (2018)
Inhibition of target digestive enzymes is an accepted strategy to prevent diseases such as obesity and diabetes. Proanthocyanidins (PACs) are known for their ability to bind, inhibit, and precipitate enzymes, which makes them potential bioDrugs with an impact on the digestive process. PAC degree of polymerization (DP) is one of the structural features responsible for their differential inhibitory potency but the explanation for this phenomenon is still unclear. Pecan nut (Carya illinoinensis L.) kernels and nutshells are rich in oligomeric and polymeric PACs. We have used thiolysis and HPLC analyses to propose four theoretical model structures of PACs representative of four semipurified fractions obtained from pecan kernel and shell, which showed different inhibitory activity against intestinal lipases, amylases, and proteases. The noncovalent interactions between PACs and digestive enzymes were predicted by in silico methods through computational software. These observations are discussed in view of current literature on the biological effects of PACs with different DPs and allowed us to propose the hypothesis that “small oligomeric PACs could be digestive enzyme inhibitors due to their capacity to enter and bind the enzymes’ specific cavities better than polymers and oligomers of medium and high molecular weight.”